Engagement Markers in Indonesian Scholars’ Academic Writing to Establish Rapport with Readers - Titah Afandi; Adi Sutrisno (Universitas Islam Negeri Palopo, 2025)
This study presents a corpus-based analysis of engagement markers in applied linguistics research articles (RAs) authored by Indonesian scholars. While previous research has explored metadiscourse broadly, this investigation focuses specifically on the strategic use of interpersonal features to build reader rapport. A specialized corpus of 20 RAs (104,110 words) from four Scopus-indexed journals (2020–2024) was compiled and analyzed using a mixed-methods approach. The analysis, conducted with the Sketch Engine tool, applied a modified version of Hyland and Jiang’s (2016) model of engagement markers. The results indicate a strong preference for knowledge-oriented engagement, with knowledge appeals being the most frequent strategy (1.59 per 1,000 words), predominantly realized through explicit markers of routine conditions. Notably, rhetorical questions were absent from the corpus. Pronominal choice revealed a distinct use of first-person plural pronouns (we, us, our) to foster solidarity and direct reader interpretation, while personal asides were employed to clarify arguments. In terms of directives, references to physical acts (e.g., “see Table 3”) were markedly more common than cognitive or textual acts. These findings suggest a stylistic convention in Indonesian academic writing that prioritizes formality and collective objectivity, potentially at the expense of more direct dialogic interaction. The study concludes by offering practical pedagogical implications for academic writing instruction, suggesting that Indonesian scholars can enhance the persuasive impact and international visibility of their work by strategically diversifying their engagement strategies to foster a more involved reader dialogue.